The power of microbes: the key role of gut microbiota in the initiation and progression of colorectal cancer - Han, Bo; Zhang, Yongfeng; Feng, Xue; Yang, Jun; Wang, Baolin; Fang, Jiang; Wang, Zhigang; Zhu, Jun; Niu, Ge; Guo, Youxiang (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) is ranked as the third most prevalent malignancy and is a leading cause of cancer-related mortality globally, significantly affecting the health and longevity of middle-aged individuals and the elderly. The primary risk factors for CRC are mainly due to unhealthy dietary habits and lifestyle choices, and they have been shown to profoundly influence the composition of the gut microbiota. Given that dietary patterns are critical determinants of gut microbial diversity, a compelling association exists between gut microbiota and the pathogenesis of CRC. Recent research has increasingly focused on the intricate interplay between gut microbiota and CRC, exploring its role in disease initiation, progression, and the modulation of host immune responses. Investigations have demonstrated that certain specific microbial communities can promote inflammation, disrupt metabolic pathways, and produce carcinogenic compounds, thereby contributing to the development of CRC. Conversely, a diverse and balanced gut microbiome may confer protective effects against cancer through mechanisms such as the production of short-chain fatty acids and the enhancement of intestinal barrier integrity. This article provides a comprehensive overview of the characteristics of the gut microbial community and its complex relationship with CRC. It highlights potential mechanisms through which gut microbiota may influence CRC pathogenesis, including chronic inflammation, toxins, metabolites, epigenetic dysregulation, and immune regulatory dysfunction. Additionally, this review summarizes innovative strategies for CRC prevention and treatment, emphasizing the therapeutic potential of probiotics and natural plant extracts. By elucidating these connections, this work aims to enhance the understanding of the gut microbiome’s role in CRC.